EVALUATION OF THE IMPLEMENTATION OF TUBERCULOSIS CONTROL POLICIES AT THE PUSKESMAS SELABATU, SUKABUMI CITY - Siti Aminah; Rizki Hegia Sampurna; Tuah Nur (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Tuberculosis (TB) remains a global health challenge, including in Indonesia, with the number of cases continuing to increase in various regions, including Sukabumi City. This study aims to evaluate the implementation of tuberculosis (TB) prevention policies at Puskesmas Selabatu in Sukabumi City using Daniel Stufflebeam's CIPP (Context, Input, Process, Product) evaluation theory. This descriptive qualitative research collected data through interviews with five key informants, observation, and documentation. The results showed that the TB control policy has been implemented with a comprehensive approach, but still faces several challenges. The results showed that tuberculosis (TB) prevention at the Selabatu Health Center was under regulations, namely Ministry of Health Regulation No. 67 of 2016 and Presidential Regulation No. 67 of 2021 and supported by the Regional Budget (APBD) and Health Operational Assistance (BOK). However, there are several obstacles in implementation, such as the capacity of medical personnel that is not yet optimal, a less effective monitoring system, and limited community education. Lack of training of TB cadres and patient monitoring that only relies on WhatsApp groups and monthly control has led to many patients being inconsistent in treatment. In addition, supporting facilities such as rapid molecular testing (TCM) are not yet available, resulting in slow early diagnosis and increasing the risk of treatment dropout. However, the DOTS approach and the active role of TB cadres helped improve patient adherence. Community participation is generally low, but if properly empowered, local communities have great potential in assisting with education, early detection, and patient monitoring. Cross-sector collaboration between Puskesmas, the Health Office, local government, and professional organizations is also important in strengthening service coordination and improving synergy in TB program implementation.